2015
DOI: 10.1155/2015/769806
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Assessment after Treatment of Nasopharyngeal Carcinoma with CRT and IMRT Techniques

Abstract: Objectives. This study analyzed the long-term hearing loss after treatment of primary nasopharyngeal carcinoma to elucidate its causal factors. Methods. Ninety-two nasopharyngeal carcinoma patients were treated with radiotherapy or chemoradiotherapy. Pure tone audiometry was performed before the therapy and annually up to 9 years after completing treatment. The hearing thresholds were corrected for age-related deterioration and compared to the results without adjusting for age. Results. The mean air and bone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
5
0
3
Order By: Relevance
“…In addition to a radiation dose of 47 Gy or more to the cochlea, the main factors affecting the risk of SNHL are the patient’s age and baseline hearing level, cisplatin dose, post-RT otitis media, and follow-up time [178,179,183185]. In addition, the deterioration in air conduction caused by RT-induced Eustachian tube dysfunction and middle air fibrosis may accompany persistent SNHL, indicating mixed hearing impairment [186]. …”
Section: Hearing Lossmentioning
confidence: 99%
“…In addition to a radiation dose of 47 Gy or more to the cochlea, the main factors affecting the risk of SNHL are the patient’s age and baseline hearing level, cisplatin dose, post-RT otitis media, and follow-up time [178,179,183185]. In addition, the deterioration in air conduction caused by RT-induced Eustachian tube dysfunction and middle air fibrosis may accompany persistent SNHL, indicating mixed hearing impairment [186]. …”
Section: Hearing Lossmentioning
confidence: 99%
“…Findings in the current literature suggest that persistent high-frequency SNHL is common after NPC treatment, and combining cisplatin-based chemotherapy with radiotherapy increases the incidence and severity of SNHL [ 5 , 6 , 9 ]. However, the existing literature is inconclusive on the nature of long-term progression of SNHL after chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that high-frequency SNHL can occur any time after the initiation of NPC treatment with occurrence probability reaching the plateau between 18 and 24 months after treatment [ 6 ]. One study suggested that treatment-induced SNHL can continue to increase with time [ 9 ]. It is noted that some of the early studies on SNHL after NPC treatment were based on short follow-up time [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modalidades de tratamento que visam minimizar a ototoxicidade devem ser estimuladas e o emprego de IMRT parece ser protetor contra a perda auditiva induzida pela radioterapia, pois permite poupar a cóclea dos efeitos das altas doses de radiação (143)(144)(145) .…”
Section: Ototoxicidadeunclassified
“…as audiometrias e os padrões de perda auditiva devem ser interpretados após ajuste para o que é esperado naquela faixa etária do paciente. Desse modo, podemos evidenciar a perda auditiva que é, verdadeiramente, uma complicação terapêutica (144) .…”
Section: Ototoxicidadeunclassified